Conflict resolution and ontological security : peace anxieties - Rumelili, Bahar (London, England : Routledge, 2015)
"This volume highlights the ways in which the prospect of peace can generate anxieties and consequently set in motion social and political processes that reproduce and reactivate conflicts. In analysing this issue, the volume builds on the notion of ont
1. Ontological (In)security and Peace Anxieties: A Framework for Conflict Resolution -- 2. Ontological Security and the Israeli-Palestinian Peace Process: Between Unstable Conflict and Conflict in Resolution -- 3. The Kurdish Issue and Levels of Ontological Security -- 4. Ethnic Nationalism and the Production of Ontological Security in Cyprus -- 5. Ontological (In)security and Violent Peace in Northern Ireland -- 6. Ontological (In)Security of 'Included' Citizens: The Case of Early Republican Turkey (1923-1946) -- 7. Ontological (In)Security After Peace: The Case of the Aland Islands -- 8. The Ontological Significance of Karelia: Finland's Reconciliation with Losing the Promised Land -- 9. Decolonising Security and Peace: Mono-Epistemology versus Peace Formation
Includes bibliographical references (p. 201) and index
Keywords: Conflict management -- Social aspects; Conflict managemen -- Social aspect -- Case studies; Ontology -- Political asepcts -- Case studies; Ontology -- Political aspects; Peace-building -- Social aspects; Peace-building -- Social aspect -- Case studies